PROGRAM BIMBINGAN PADA ANAK TUNAGRAHITA DAN AUTIS MELALUI TERAPI BERMAIN UNTUK MENGEMBANGKAN PERILAKU ADAPTIF DI SLB NEGERI UNGARAN - Adimayanti, Eka; Siyamti, Dewi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2019)
Every child has different characteristics, strengths, weaknesses, and abilities and levels of disability.Children with special needs need special assistance for learning. Assistance can be done when thechild is playing. Play can improve children's abilities, both cognitive, affective and psychomotorabilities. Abilities that we can value in children with special needs through mentoring to playadaptive abilities. This study aims was to determine the overview of the guidance program throughplay therapy in children with special needs in SLB Negeri Ungaran. This study used a descriptiveresearch design with a qualitative approach. In its implementation there were quantitativecategorizations, and concluded with qualitative descriptions. Selection of respondents who met theinclusion criteria, namely retarded children and children with autism aged 4-11 years. Respondentswould be assessed using the VSMS questionnaire consisting of 117 items of question orders at thetime before and after the intervention play therapy guidance. The results of this study illustrated theincrease in students' adaptive abilities in general self help, self eating, self dressing, self direction,locomotion, occupation, socialization and communication. Conclusion: the provision of guidancemethods through play therapy can provide stimulus to retarded and autistic students to improve dailyadaptive behavior.